Analysis of Determinant Factors of Occupational Safety and Health Culture at PT.Energi Sengkang - Rahman Rahman; Yahya Thamrin; Andi Surahman Batara (PT.Mantaya Idea Batara, 2021)
Safety culture is a combination of characteristics and attitudes in the organization which is an integration of behavior, attitudes and performance that can move the organization. This research method is Mixed Methods with sequential explanatory design, data analysis using Logistic Regression test, sampling technique by purposive sampling with a sample of 68 people. The results of the study show that the leadership variable has a significance value of 0.044 with Exp(B) of 4.290, the Teamwork variable has a significance value of 0.031 with Exp(B) of 4.726, the Employee Engagement variable has a significance value of 0.033 with Exp(B) of 4.486, the Policy variable has a significance value of 0.048 with Exp(B) of 3.814, the Technology variable has a significance value of 0.042 and Exp(B) of 4.234 and the Communication variable has a significance value of 0.037 and Exp(B) of 4.334. The conclusion in this study is based on a significance value of 0.05. Leadership is a determinant factor in the K3 culture at PT. Sengkang Energy, Teamwork is a determining factor in the K3 culture at PT. Energy Sengkang, Employee Involvement is a determining factor in the K3 culture at PT. Energy Sengkang, Policy is a determinant factor in the culture of K3 at PT. Sengkang Energy, Technology is a determining factor in the K3 culture at PT. Sengkang Energy and Communication are determinant factors in the OSH culture at PT. Sengkang Energy.